Exposure to alternative bisphenols BPS and BPF through breast milk: Noxious heritage effect during nursing associated with idiopathic infertility - Nevoral, Jan; Havránková, Jiřina; Kolinko, Yaroslav; Prokešová, Šárka; Fenclová, Tereza; Monsef, Ladan; Žalmanová, Tereza; Petr, Jaroslav; Králíčková, Milena (Toxicology and applied pharmacology, 2021)
There is increasing evidence that bisphenols BPS and BPF, which are analogues of BPA, have deleterious effects on reproduction even at extremely low doses. Indirect exposure via the maternal route (i.e. across the placenta and/or by breastfeeding) is underestimated, although it can be assumed to be a cause of idiopathic female infertility. Therefore, we hypothesised the deleterious effects of exposure to BPA analogues during breastfeeding on the ovarian and oocyte quality of offspring. A 15-day exposure period of pups was designed, whilst nursing dams (N ≥ 6 per experimental group) were treated via drinking water with a low (0.2 ng/g body weight/day) or moderate (20 ng/g body weight/day) dose of bisphenol, mimicking real exposure in humans. Thereafter, female pups were bred to 60 days and oocytes were collected. Immature oocytes were used in the in-vitro maturation assay; alternatively, in-vivo-matured oocytes were isolated and used for parthenogenetic activation. Both in-vitro- and in-vivo-matured oocytes were subjected to immunostaining of spindle microtubules (α-tubulin) and demethylation of histone H3 on the lysine K27 (H3K27me2) residue. Although very low doses of both BPS and BPF did not affect the quality of ovarian histology, spindle formation and epigenetic signs were affected. Notably, in-vitro-matured oocytes were significantly sensitive to both doses of BPS and BPF. Although no significant differences in spindle-chromatin quality were identified in ovulated and in-vivo-matured oocytes, developmental competence was significantly damaged. Taken together, our mouse model provides evidence that bisphenol analogues represent a risk to human reproduction, possibly leading to idiopathic infertility in women.
Keywords: ovariální rezerva; Lactation; Mice, Inbred ICR; Oocyte maturation; mléko; Phenols; In Vitro Oocyte Maturation Techniques; Benzhydryl Compounds; epigeneze genetická; těhotenství; vývojová regulace genové exprese; fertilita; ženská infertilita; Epigenesis, Genetic; benzhydrylové sloučeniny; Risk Assessment; Maternal Exposure; sulfony; Mice; Spindle Apparatus; fenoly; Sulfones; aparát dělícího vřeténka; Spindle formation; Gene Expression Regulation, Developmental; Infertility, Female; Oocytes; ženské pohlaví; hodnocení rizik; zvířata; oocyty; IVM techniky; myši inbrední ICR; Pregnancy; Bisphenol; Animals, Suckling; Fertility; ovarium; Ovary; Epigenetics; laktace; myši; Milk; Ovarian Reserve; matka - expozice noxám; Female; kojená zvířata; Animals